1999
DOI: 10.1007/bf03403539
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmodium vivax Vaccine Candidate Displays Limited Allele Polymorphism, Which Does Not Restrict Recognition by Antibodies

Abstract: Background: The 19 kDa C-terminal region of the merozoite surface protein 1 (MSP1 19) has been suggested as candidate for part of a subunit vaccine against malaria. A major concern in vaccine development is the polymorphism observed in different plasmodial strains. The present study examined the extension and immunological relevance of the allelic polymorphism of the MSP119 from Plasmodium vivax, a major human malaria parasite. Materials and Methods: We cloned and sequenced 88 gene fragments representing the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 49 publications
(57 reference statements)
1
17
0
2
Order By: Relevance
“…We also detected high proportions of anti-PvMSP-1 19 IgG (>70%) in subjects living in different localities in the Brazilian endemic area despite of the level of malaria exposure. Our data confirm the high immunogenicity of this molecule probably due to: (1) its maintenance on the merozoite membrane during the invasion process or (2) its restricted polymorphism (Pasay et al 1995;Soares et al 1999c). We also confirm the little boosting effect to …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also detected high proportions of anti-PvMSP-1 19 IgG (>70%) in subjects living in different localities in the Brazilian endemic area despite of the level of malaria exposure. Our data confirm the high immunogenicity of this molecule probably due to: (1) its maintenance on the merozoite membrane during the invasion process or (2) its restricted polymorphism (Pasay et al 1995;Soares et al 1999c). We also confirm the little boosting effect to …”
Section: Discussionsupporting
confidence: 89%
“…The recombinant P. vivax MSP-1 19 (PvMSP-1 19 ) protein which represents the amino acid sequence of the two EGF-like motifs of the Bele´m strain was expressed in Escherichia coli in fusion with the Glutathione S-transferase (GST) gene as described previously (Soares et al 1999c;Cunha et al 2001). …”
Section: Antigensmentioning
confidence: 99%
“…This observation was subsequently confirmed in studies performed in Korea, where more than 90% of P. vivax -infected individuals displayed specific antibodies to P. vivax MSP1 19 [9]. Also important was the observation that the P. vivax MSP1 19 gene displays very limited allele polymorphism in different regions of the world that does not restrict recognition by human antibodies [10,11]. Together, these results suggested that it could be possible to develop an ELISA using a single recombinant protein based on the P. vivax MSP1 19 .…”
Section: Introductionmentioning
confidence: 86%
“…Bacterial recombinant proteins expressed in the pET vector (His 6 MSP1 19 ) retained native epitopes being recognized by antibodies of 93.5% of Brazilian individuals exposed to P. vivax malaria [13]. The addition of a synthetic universal T-cell epitope denominated Pan Allelic DR epitope (PADRE) did not modify the MSP1 19 epitopes recognized by human naturally acquired IgG [11,13] and improved the performance of several adjuvant formulations when the antigen was administered to a mouse strain, such as C57BL/6, which develops PADRE-specific helper CD4 T cells [14].…”
Section: Introductionmentioning
confidence: 99%